Biomechanical Impact of a Zygoma Complex Fracture Using Human Cadaver. Issue 6 (September 2021) - Ip, Kenneth K.C.; You, Peng; Ferreira, Louis M.; Moore, Corey C.
Abstract : Abstract: Zygomaticomaxillary complex fractures are common in midface trauma, with treatment often involving repair using titanium mini plates. However, the need for plate fixation along the zygomaticomaxillary suture on the infraorbital rim remains controversial. This study utilized a previously reported bite force simulator to investigate craniofacial strain patterns following zygomaticomaxillary complex fracture repairs with and without plating of the infraorbital rim. Osteotomies were made to 6 fresh-frozen cadaveric heads to simulate 2 types of zygomatic complex fractures: a dipod fracture with osteotomies at the zygomaticofrontal and zygomaticomaxillary sutures, and a tripod fracture with an additional osteotomies at the zygomaticotemporal suture. Repairs with and without the use of a titanium mini plate across the infraorbital rim were compared in both dipod and tripod fractures. Physiologically proportional masticatory loads were applied using the bite force simulator by actuating intrinsic muscle lines of action. The outcome metric was facial bone strains measured using uniaxial strain gauges. Mixed-effects linear models did not find a significant main effect on the overall strain pattern with the use of an infraorbital rim plate in both dipod ( P = 0.198) and tripod ( P = 0.117) fracture repairs. However, statistically significant differences were found locally at the zygomatic buttress ( P = 0.019) and the zygomatic arch ( P = 0.027) on the fractured side in dipod fractures. This is the first known study that successfully utilized a mechanical simulator to reproduce physiological intrinsic masticatory loads in a fracture fixation study. This new technology opens avenues for future biomechanical investigations on maxillofacial fracture repairs and other surgical treatments. Abstract : Supplemental Digital Content is available in the text